Relationship between onset age of type 2 diabetes mellitus and vascular complications based on propensity score matching analysis. Issue 6 (11th March 2022) - Huang, Lingning; Wu, Peiwen; Zhang, Yongze; Lin, Yanxian; Shen, Ximei; Zhao, Fengying; Yan, Sunjie
Abstract: Aims/Introduction: To assess the relationship between type 2 diabetes mellitus onset age and vascular complications in China. Materials and Methods: A retrospective review of 3, 568 patients with type 2 diabetes mellitus using a propensity score‐matched (PSM) cohort analysis was carried out in two different age of onset groups (age 40 and 60 years). These groups were then subdivided into two groups, early‐onset diabetes (EOD40 and EOD60; the onset age before 40 and 60 years, respectively) and late‐onset diabetes (LOD40 and LOD60: the onset age after 40 and 60 years, respectively). Macrovascular and microvascular complications were analyzed before and after PSM. Results: Patients categorized in both the early‐onset disease (EOD) groups had a higher risk of developing macro‐ and microvascular complications before PSM. After PSM, no differences existed between the EOD and late‐onset disease groups in the risk of macrovascular complications. Compared with the late‐onset disease group, the odds ratio of having a microvascular complication of diabetic retinopathy, chronic kidney disease and diabetic peripheral neuropathy in the 40‐year‐old EOD group increased to 2.906, 1.967 and 1.672 ( P < 0.05), respectively. The odds ratio of diabetic retinopathy and diabetic peripheral neuropathy in the 60‐year‐old EOD group was 1.763 and 1.675 ( P < 0.05), respectively. Conclusions: The earlier the onset of type 2 diabetes mellitus, the higher risk of microvascular, but not necessarily macrovascular, complications. It is not too late to prevent diabetes at any age. Pre‐emptive microvascular treatment or preventative measures in EOD patients who do not yet show symptoms, might be beneficial. Abstract : A retrospective review of 3, 568 patients with T2DM using a propensity score‐matched (PSM) cohort analysis, based on age and gender, was performed in two different age of onset groups (40 and 60 years old). The earlier onset of T2DM the higher risk of microvascular but not necessarily macrovascular complications. Preemptive microvascular treatment or preventative measures in EOD patients who do not yet show symptoms, may be beneficial.